COVID-19: The impacts of the global crises on African remittances and countries response to this an extreme crisis - Andualem Kassegn (Cogent Economics & Finance, 2021)
As the COVID-19 pandemic continues to afflict much of the global economy, the flow of African remittances is likely to suffer substantially. Therefore, the aims of this review were to assess and complied the possible impacts of the COVID-19 pandemic on African remittances and highlights the key responses undertaken in the continent, which could be useful and provided necessary information on the ongoing COVID-19 pandemics in the continent. To achieve these objectives, in this review, all relevant information were collected through different search engines of PubMed/PMC/Medline, Web of Science, Google Scholar, Scopus, Google, and Science Direct databases. In addition, media news, reports relevant to the topic from local and national governments and international organizations were used. This review revealed that the COVID-19 pandemic is inevitably affecting remittance-dependent African countries through devastating impacts on the global economy in the destination countries, and restrictions on travel and high cost of sending remittances to their home country.As aresult, remittances to Africa are expected to decrease significantly by around 8.8% between 2019 and 2020, from 48 billion to 44 billion. Hence, this review draws practical lessons for African countries to tackle the impacts of COVID-19 pandemic on African remittance inflows. It argues that governments need to design and undertaken comprehensive relief measures, monetary and fiscal policy recovery policies to address problems related to the falling of remittances towards Africa due to the pandemic. Therefore, flexible country level and region-wide collaborative efforts should be made to mitigate the expected decline of remittance inflows to African due to the COVID-19 pandemic.
Keywords: 330; Africa; COVID-19; crises; impacts; policies; remittances